Deep order-wavelet convolutional variational autoencoder for fault identification of rolling bearing under fluctuating speed conditions - Yan, Xiaoan; She, Daoming; Xu, Yadong (Expert systems with applications, 2023)
•A novel model named DOWCVAE is proposed for bearing fault identification.•An optimizer hailed as MOGWO is introduced for parameter adaptive selection.•Our model can adapt well to fault diagnosis task under fluctuating speeds.•Two experimental cases are adopted to validate the effectiveness of our model. Because of the complex operating environment of high-end industrial machinery, rolling bearing is generally operated at fluctuating working conditions such as variable speeds or loads, thus enables fault feature information is not obvious. That said, bearing fault identification under fluctuating working conditions are recognized as a very challenging problem. Deep learning blazes a valid route to address this issue by right of strong self-learning performance. Nevertheless, the performance of traditional deep learning model will degrade in the face of the fluctuating data with a sharp rising and heavy external interference. Therefore, to overcome this limitation, this study proposes a novel method named deep order-wavelet convolutional variational autoencoder (DOWCVAE) to identify bearing faults under fluctuating speed conditions, which can improve feature learning ability of a plain convolutional variational autoencoder (CVAE). Within this approach, an improved energy-order analysis with frequency-weighted energy operator (FWEO) is firstly presented to convert the raw time-domain vibration signal into the resampled angle-domain signal to relieve the influence of speed fluctuating and acquire the enhanced order spectrum data. Afterwards, wavelet kernel convolutional block (WKCB) with anti-symmetric real Laplace wavelet (ARLW) is constructed to extract the latent feature information closely related to equipment states from the enhanced order spectrum data via the stacked way layer by layer, which is capable of further promoting learning performance of overall network model and improve its generalizability. In addition, a high-efficiency intelligent optimization algorithm termed as multi-objective gray wolf optimizer (MOGWO) is introduced for choosing automatically optimal wavelet parameters of DOWCVAE model and avoiding negative impact posed by artificially adjusting parameter. Ultimately, the learned latent features are loaded to the softmax classifier to achieve automatic identification of different bearing health states and provide comprehensive diagnosis result. The analysis results from two experiment cases testify the effectiveness of our approach. Quantitatively, average identification accuracy of the proposed approach can reach 99% above, which shows its competitive advantages and is more satisfying as compared to some representative deep learning methods.